2016
DOI: 10.1590/s0104-59702016000100003
|View full text |Cite
|
Sign up to set email alerts
|

The biomedicalisation of illegal abortion: the double life of misoprostol in Brazil

Abstract: A biomedicalização do aborto ilegal: a vida dupla do misoprostol no BrasilRecebido para publicação em outubro de 2014. Aprovado para publicação em junho de 2015.http://dx.doi.org/10.1590/S0104-59702016000100003 DE ZORDO, Silvia. The biomedicalisation of illegal abortion: the double life of misoprostol in Brazil. História, Ciências, Saúde -Manguinhos, Rio de Janeiro, v.23, n.1, jan.-mar. 2016, p.19-35. Abstract This paper examines the double life of misoprostol in Brazil, where it is illegally used by wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 25 publications
(18 reference statements)
3
43
0
13
Order By: Relevance
“…; De Zordo et al. ; Mishtal ). Similarly, women themselves engage with transnational discourses around rights and modernity in addition to local moral cosmologies to situate their own abortion histories within new articulations of gendered personhood (Amuchástegui and Flores ; Andaya ; Gammeltoft ; Paxson ).…”
Section: New Sites For Anthropological Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…; De Zordo et al. ; Mishtal ). Similarly, women themselves engage with transnational discourses around rights and modernity in addition to local moral cosmologies to situate their own abortion histories within new articulations of gendered personhood (Amuchástegui and Flores ; Andaya ; Gammeltoft ; Paxson ).…”
Section: New Sites For Anthropological Engagementmentioning
confidence: 99%
“…In the face of this assault on abortion availability and access, we call for anthropologists to engage with this shifting landscape of reproductive politics in the United States (Council on Anthropology and Reproduction ). Anthropologists concerned with the politics of reproduction have examined access and meanings attached to abortion in various global sites (see Andaya ; De Zordo ; Gammeltoft ; Ginsburg ; Johnson‐Hanks ; Mishtal ; Morgan ; Paxson ; Rylko‐Bauer ). In the United States, however, a review of existing scholarship shows that abortion research has largely moved to other fields with more narrowly defined research questions, in particular public health, demography, sociology, and legal studies .…”
mentioning
confidence: 99%
“…In the 1980s and 90s, anthropological studies found women were attempting to induce abortion by using drugs contraindicated during pregnancy, such as antimalarials 19 and misoprostol, a prostaglandin on the market to treat ulcers. 20 …”
Section: Fertility Managementmentioning
confidence: 99%
“…Children who had been exposed to valproate in utero had significant lower IQ scores compared to the other drugs, an effect that was shown to be dose‐dependent. At 6 years of age those children had reduced verbal and memory abilities 25‐28,40,45‐78 …”
Section: Introductionmentioning
confidence: 99%